2013
DOI: 10.5171/2013.197440
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Purchase Intentions and Honey Related Products

Abstract: Honey products have been developing from health supplements field to economic development field. There are numerous of explanations when it comes to exploring the factors that influence consumers to consume honey products. The portrayal of honey congregated importance ever since it has been commonly used in both medical and domestic needs and as well as beauty needs. In peoples' perspective, the quality of the product will be the key success factor of honey product where industries of honey maker faced challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
7
34
0
2
Order By: Relevance
“…Similar to other studies [78], respondents recognized honey as a natural sweetener and this assumed a very important factor for honey consumption. Honey, in fact, starting from the origin of human history, has been considered as one of the most energy-rich and sweetest foods in nature [26].…”
Section: Discussionsupporting
confidence: 80%
“…Similar to other studies [78], respondents recognized honey as a natural sweetener and this assumed a very important factor for honey consumption. Honey, in fact, starting from the origin of human history, has been considered as one of the most energy-rich and sweetest foods in nature [26].…”
Section: Discussionsupporting
confidence: 80%
“…However, the present study also indicated that the levels of protein and total phenolic content of honey of Tetrigona binghami species are significantly higher while the reducing sugar is relatively low compared to honey of Heterotrigona itama. According to Yeow et al (2013), many factors influence the consumers' buying behaviours of honey and honey related products. The factors are product quality, medical conditions, brand reputation and pricing.…”
Section: Resultsmentioning
confidence: 99%
“…Farms operating under organic farming regimes are also encouraged to adopt biotechniques rather than common, legal commercial treatments, because it is possible to obtain a supplemental income (nucleus sale/colony stock conservation). This addresses the behavior of beekeepers, who are increasingly interested in the quality of honey as well as other bee products, because quality is an attribute gaining consideration by consumers, as shown in [5,7,8]. Furthermore, if carried out at an early stage, the TBR technique can lead to a reduction in honey production compared to hives managed by other methods.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the rest of the European Union, Italy shows a substantial comparative disadvantage in the trade of this product [4], and imports honey from abroad, especially from Argentina and Hungary, where it can be produced at lower costs. Consumers are interested in the quality of honey [5,6], in other bee products [7], and also in where the honey is produced [8,9]. Organic honey is increasingly appreciated by European consumers [8].…”
Section: Introductionmentioning
confidence: 99%